KARAKTERISTIK FISIK DAN SENSORIS ES KRIM KACANG MERAH (Phaseolus vulgaris L.) DENGAN PENAMBAHAN TEPUNG UMBI GEMBILI (Dioscorea esculenta L.) SEBAGAI PENSTABIL - Cicilia Nuryati; Anang Mohammad Legowo; Nurwantoro Nurwantoro (Faculty of Agricultural Technology, University of Jember, 2020)
Gembili tubers are Dioscoreaceae plants which contain mucus which is water soluble polysaccharide (13.42% db), able to bind materials and form gels, and is glucomannan (Harijono et al., 2010; Prabowo et al., 2014). Gembili tubers can be used as a stabilizer, thickener, and also gelling agent in ice cream products because of this content. This research aims to determine the effect of added gembili tuber flour with different concentrations on overrun, melting speed, total solids, and hedonic quality of red bean ice cream. The material used is red bean porridge, fresh cow's milk, granulated sugar, whipped cream, egg yolks, water, and gembili tuber flour. The experimental design used was a Completely Randomized Design (CRD) with 5 treatments and 4 replications with a formulation of adding gembili tuber flour concentration of 0%, 2%, 4%, 6%, 8%. Analysis of the data used is the Analysis of Variants (ANOVA) at a significance level of 5%. The results showed that the addition of different concentrations of gembili tuber flour to peanut ice cream had a significant effect (P <0.05) on overrun, melting speed, and total solids, as well as texture, taste, and thickness characteristics but did not significantly affect the color, aroma, and favorite overalls. The best treatment of added gembili tuber flour as a stabilizer of red bean ice cream is 0.4%. Keywords: gembili tubers, hedonics, ice cream, kidney beans, overrun